NAC Pre-Administration Prevents Cardiac Mitochondrial Bioenergetics, Dynamics, Biogenesis, and Redox Alteration in Folic Acid-AKI-Induced Cardio-Renal Syndrome Type 3 - Belén Cuevas-López; Edgar Ignacio Romero-Ramirez; Fernando E. García-Arroyo; Edilia Tapia; Juan Carlos León-Contreras; Alejandro Silva-Palacios; Francisco-Javier Roldán; Omar Noel Medina Campos; Luz Hernandez-Esquivel; Alvaro Marín-Hernández; José Guillermo Gonzaga-Sánchez; Rogelio Hernández-Pando; et al. (MDPI AG, 2023)
The incidence of kidney disease is increasing worldwide. Acute kidney injury (AKI) can strongly favor cardio-renal syndrome (CRS) type 3 development. However, the mechanism involved in CRS development is not entirely understood. In this sense, mitochondrial impairment in both organs has become a central axis in CRS physiopathology. This study aimed to elucidate the molecular mechanisms associated with cardiac mitochondrial impairment and its role in CRS development in the folic acid-induced AKI (FA-AKI) model. Our results showed that 48 h after FA-AKI, the administration of N-acetyl-cysteine (NAC), a mitochondrial glutathione regulator, prevented the early increase in inflammatory and cell death markers and oxidative stress in the heart. This was associated with the ability of NAC to protect heart mitochondrial bioenergetics, principally oxidative phosphorylation (OXPHOS) and membrane potential, through complex I activity and the preservation of glutathione balance, thus preventing mitochondrial dynamics shifting to fission and the decreases in mitochondrial biogenesis and mass. Our data show, for the first time, that mitochondrial bioenergetics impairment plays a critical role in the mechanism that leads to heart damage. Furthermore, NAC heart mitochondrial preservation during an AKI event can be a valuable strategy to prevent CRS type 3 development.